Eficiência de goma gelana na estabilidade física de suco tropical de cagaita - Corrêa, Nayara Canedo; Campos, Marizete Aparecida da Cunha; Barbosa, Thaís Alves; Souza, Eli Regina Barboza de; Siqueira, Ana Paula Silva (Multi-Science Journal, 2017)
Não há.